Direct comparisons of European primary and secondary frequency standards via satellite techniques. (21st July 2020) - Riedel, F; Al-Masoudi, A; Benkler, E; Dörscher, S; Gerginov, V; Grebing, C; Häfner, S; Huntemann, N; Lipphardt, B; Lisdat, C; Peik, E; Piester, D; et al.
Abstract: We carried out a 26-day comparison of five simultaneously operated optical clocks and six atomic fountain clocks located at INRIM, LNE-SYRTE, NPL and PTB by using two satellite-based frequency comparison techniques: broadband Two-Way Satellite Time and Frequency Transfer (TWSTFT) and Global Positioning System Precise Point Positioning (GPS PPP). With an enhanced statistical analysis procedure taking into account correlations and gaps in the measurement data, combined overall uncertainties in the range of 1.8 × 10 −16 to 3.5 × 10 −16 for the optical clock comparisons were found. The comparison of the fountain clocks yields results with a maximum relative frequency difference of 6.9 × 10 −16, and combined overall uncertainties in the range of 4.8 × 10 −16 to 7.7 × 10 −16 .